TRACE LEVEL QUANTIFICATION OF C1-C3 ALKYL CHLORIDE GENOTOXIC IMPURITIES IN TRIMETAZIDINE DI HYDROCHLORIDE DRUG SUBSTANCE USING STATIC HEADSPACE GAS CHROMATOGRAPHY - RAJAVENKATA PRASAD PATHA; KARUNAKAR DASA; RAMA DEVI BHOOMIREDDY; RAVI KIRAN PANCHAKARLA; RAJ KUMAR KOKKONDA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objective of this study was to develop and validate a gas chromatography-headspace (GC-HS) method for the quantification of genotoxic alkyl chloride impurities (chloromethane, ethyl chloride, and isopropyl chloride) in trimetazidine dihydrochloride, ensuring compliance with International Council for Harmonization M7 guidelines. Methods: A GC-HS method was optimized using a DB-1 column (60 m×0.32 mm, 3.0 μm) with nitrogen as the carrier gas. Key parameters included HS conditions with an oven temperature of 95°C, sample line temperature of 105°C, and transfer line temperature of 115°C, along with a split ratio of 1:10 and a flow rate of 10.2 psi. The oven temperature program was set to start at 40°C for 15 min, followed by an increase of 30°C/min to 250°C, held for 15 min. Method validation assessed linearity, detection limits, quantification limits, accuracy, precision, and solution stability. Results: The method exhibited excellent linearity (r²>0.999), low limits of detection (0.6 ppm) and quantification (1.8 ppm), and high accuracy (91.0–114.0% recovery). Precision was confirmed with relative standard deviations below 5%. Sample solutions remained stable for up to 48 h, demonstrating the method’s robustness and reliability for routine analysis. Conclusion: The developed GC-HS method is a robust, accurate, and regulatory-compliant approach for the trace-level quantification of genotoxic alkyl chloride impurities in trimetazidine dihydrochloride, ensuring the safety and quality of the pharmaceutical product.